Diversity and morphological adaptations of tropical dry forest's lichens and bryophytes in Colombia (2018)
Xerophytic environments, and more specifically, the Colombian dry tropical forest exhibits various conditions that causes intense selective pressures, some example are: a high evapotranspiration rate, intense radiation and low relative humidity (RH). As a consequence of these characteristic conditions, a diverse species radiation has arisen across the Caribbean Valley. Among other groups, the lichens and mosses have made a thorough colonization of the differential strata of this habitat. The area's average temperature is 36aC, and possesses a low RH, which have resulted in several morphological differences among the bryophytes, such as lumen area and wall width. For this study the local diversity was evaluated by collection of specimens in a minimum disturbed dry forest, in both, dry and humid season for two years. After collection, the different species were characterized using microscopic analysis, with the bryophytes undergoing further testing along a transpiration essay by gravimetrical method. Thus, understanding the exaptations leading to their colonization as pioneer organisms. Overall, 13 species of lichens and 10 species in the Bryophyta clade found. The exaptations presented in the various bryophytes found were presence of mammillae/papillae, while most of the lichens were lecanorine, perhaps providing insight in the most advantageous apomorphies for the survival of these organisms in the dry tropical forest